SISTEM PENGENDALIAN INTERN ATAS PENGELOLAAN PERSEDIAAN BARANG GUDANG DENGAN APLIKASI MAXIMO PADA PT PLN (PERSERO) UPDK KERAMASAN - Nugroho Kuncoro Guritno; Maulan Irwandi; Auliani Auliani; Nia Masnita Sari; Rosaria Yusepha (Politeknik Negeri Sriwijaya, 2021)
This study describes the application of the elements of the internal control system to the procedure for receiving and releasing goods in the warehouse using the Maximo application at PT PLN (Persero) Keramasan Generation Control Executing Unit (UPDK). The internal control system is a system that was formed to suppress the targets to be achieved by the company, and not to emphasize the elements of the system. Internal control can increase the level of efficiency, prevent loss of assets, improve accounting data, and improve compliance with applicable regulations. Based on observations, it shows that PT PLN (Persero) UPDK Keramasan has implemented internal controls on the procedures for receiving and releasing goods in the warehouse using Maximo